Effects of Morelloflavone from Garcinia dulcis on Vasorelaxation of Isolated Rat Thoracic Aorta - Lamai, Jarunet; Mahabusarakam,, Wilawan; Ratithammatorn, Thanaporn; Hiranyachattada, Siriphun (Journal of Physiological and Biomedical Sciences, 2013)
Morelloflavone is a flavonoid isolated from Garcinia dulcis, Kurz., an Asian medicinal plant used to treat a sore throat, scurvy and cough. Previous in vitro experiments have shown that morelloflavone possesses anti-inflammatory, anti-oxidant and anti-bacterial properties while other pharmacological effects have never been researched. This work aimed to investigate the action and mechanism(s) of morelloflavone from G. dulcis on relaxation of isolated rat thoracic aorta precontracted with norepinephrine (1 g resting tension). Cumulative addition of 10-9-10-5 M morelloflavone significantly relaxed the precontracted aortic rings in a dose-dependent manner with a maximal relaxation of 77.5±5.4% and an EC50 of approximately 10-7 M. In denuded rings, this effect was abolished. Pre-incubation of endothelium-intact aortic rings with 10-6 M L-NOARG, a nitric oxide synthase inhibitor, significantly abolished morelloflavone-induced vasorelaxation, while the cyclooxygenase inhibitor indomethacin (10-6 M) had no effect. Morevover, either 10-5 M glibenclamide (an ATP-sensitive K+ channel inhibitor) or 10-3 M TEA (a non-selective Ca2+-activated K+ channel blocker) could partially inhibited morelloflavone-induced vasorelaxation. Therefore, the vasorelaxation mechanism of morelloflavone was endothelium-dependent which involved nitric oxide signaling pathway and, partly, ATP-sensitive and Ca2+-activated K+ channels.